2020
DOI: 10.5603/cj.a2018.0077
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of endothelial function between conduit artery and microvasculature in patients with coronary artery disease

Abstract: Present results suggest that noninvasive assessment of vascular endothelial functions provide pathophysiological information on both conduit arteries and resistance vessels in patients with CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The endothelial dysfunction in the large conduit arteries and resistance small vessels have been reported to have different correlations with cardiovascular risk factors and may be unrelated to one another, suggesting differential regulation of endothelial function in these two vascular beds 8,17,18,28,29 . The discrepancy between macro- and microvascular dysfunction could be explained by the fact that they may mirror different stages of disease 8,30 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The endothelial dysfunction in the large conduit arteries and resistance small vessels have been reported to have different correlations with cardiovascular risk factors and may be unrelated to one another, suggesting differential regulation of endothelial function in these two vascular beds 8,17,18,28,29 . The discrepancy between macro- and microvascular dysfunction could be explained by the fact that they may mirror different stages of disease 8,30 .…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between macro-and microvascular dysfunction could be explained by the fact that they may mirror different stages of disease 8,30 . The endothelial dysfunction in conduit arteries can reflect a process of existing CAD, while microvascular dysfunction may be a prognostic biomarker, which may precede endothelial impairment in large arteries and the subsequent clinical manifestations [8][9][10]30 . For example, several studies have highlighted the detection of microvascular dysfunction as potentially clinically relevant for the early diagnosis of microvascular disorders, before macrovascular disease 11,31,32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed simultaneous measurement of FMD and RHI within 7 days before cardiac catheterization, as previously described (Tomiyama et al 2014;Tajima et al 2020). In brief, subjects were instructed to fast overnight and to abstain from alcohol, smoking, caffeine and antioxidant vitamins for at least 12 hours prior to measurements.…”
Section: Simultaneous Measurement Of Fmd and Rhimentioning
confidence: 99%
“…Although both FMD and RHI measurements can predict cardiovascular events, the clinical significance of these two vascular endothelial function tests in patients with cardiovascular diseases may be different, as these methods measure vascular function in different vessels (conduit arteries or microvasculature). Using a method of simultaneous measurement, we recently reported that both FMD and RHI were not correlated in patients with ischemic heart disease (IHD) (Tajima et al 2020). However, there have been no previous reports on vascular endothelial function of both conduit arteries and microvasculature measurements via FMD and RHI in patients with HF.…”
Section: Introductionmentioning
confidence: 99%